Consumer preferences for end-use specific curtailable electricity contracts on household appliances during peak load hours - Jason Harold; Valentin Bertsch; Harrison Fell (The Economic and Social Research Institute (ESRI), 2019)
Growth in energy demand together with the expansion of variable renewables has significant implications for the future electricity system. The increased volatility from growing intermittent production requires new sources of flexibility at a much greater scale to help maintain system balance. In particular, it is necessary to encourage demand reduction during peak load periods in order to avoid high cost capital investments in accommodating future peak capacity. Curtailable electricity contracts are one incentive-based Demand Response (DR) instrument that could help increase demand flexibility in the residential sector. Specifically, end-use specific curtailable contracts work by curtailing the household load directly related to the final energy service provided, for example a washing machine. To help understand consumer preferences for these types of contracts, this paper employs a discrete choice experiment on a large representative sample of electricity consumers to elicit their preferences for end-use specific curtailable contracts on different household appliances during the peak load hours between 5pm and 8pm in the evening. Furthermore, this paper estimates the compensations required by consumers to accept curtailable contracts and conducts a welfare analysis from the consumer's standpoint to determine the welfare effects for 96 different contract scenarios. In general, there is a large potential for demand flexibility from end-use specific curtailable contracts with consumers found to prefer curtailable contracts compared to their status quo electricity contracts on average. More specifically, the results show that the type of household appliance in these contracts has the most influence on consumer's preferences. The findings also suggest that consumers prefer contracts at low event frequencies that also include advance notice and an opt out. Overall, the compensations required for such contracts are estimated to be comparatively reasonable to other contract types examined in the literature.
Keywords: D12; Q4; Q5; 330; curtailable contracts; electricity market; household appliances; demand response; choice experiment; energy policy